Immunohisto Chemical Expression of IDH1, ATRX and P53 in Low Grade Diffuse Gliomas at Armed Forces Institute of Pathology, Rawalpindi - Arif, Ayesha; Akhtar, Farhan; Ahson, Ahmed; Uddin, Hafeez; Ahmed, Rabia; Ahmed, Aminah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the immune histochemical expression of IDH1, ATRX and p53 in low-grade diffuse gliomas. Study Design: Cross-sectional study. Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jan to Jun 2020. Methodology: Forty-two cases of low-grade diffuse glioma were included in the study. The cases were stratified into diffuse astrocytoma and oligodendroglioma based on results of immunohistochemistry expression for IDH1, ATRX and p53. Results: The frontal lobe was the most commonly affected site 14 (33.3%). Based on the results of immunohistochemistry expression, 26 cases (61.9%) were diagnosed as an oligodendroglioma, while 16 cases (38.1%) were diagnosed as diffuse astrocytoma. All cases were assigned who grade II out of IV. In oligodendrogliomas, all cases (100%) were IDH1 mutants with the retained expression of ATRX and wild type expression of p53. Among the 16 cases of diffuse astrocytoma, IDH1 was mutant in 12 cases (75%), ATRX expression was lost in all cases, and p53 was mutant in 6 cases (37.5%). Conclusion: The study showed that low-grade diffuse gliomas could be stratified and sub-classified in accordance with the World Health Organization (WHO) classification of CNS tumours (2016) successfully by application of immunohistochemistry for IDH1, ATRX and p53.